2016
DOI: 10.1080/01694243.2016.1157431
|View full text |Cite
|
Sign up to set email alerts
|

A fatigue life prediction method of adhesively bonded joints based on visco-elastic and visco-plastic behavior: application under cyclic shear loading

Abstract: International audienceTo perform an evaluation of the abilities of a bonded structure to endure repetitive loadings, characterizations of structural adhesive joints mechanical behavior are key objectives. The aim of this study is to describe the phenomena occurring in the bonded joint until the appearance of a macroscopic crack. Using lap-shear type specimens, associated with stress concentrations, crack initiation generally appears early at the edge of the adhesive joint, which makes it difficult to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Some adhesives behave differently in tension and compression because of the influence of hydrostatic stress on the nonlinear behaviors. Several experimental investigations involving multiaxial stress states, such as Arcan joints (Bidaud et al 2016;Suwanpakpraek et al 2020), lap shear joints (Srinivasan, Ravichandran, and Idapalapati 2020;Zgoul and Crocombe 2004), scarf joints (Afendi, Teramoto, and Bakri 2011;Carrere et al 2015), and tubular butt joints (Arnaud, Créac'Hcadec, and Cognard 2014;Cognard et al 2012), have shown that the yield and failure of adhesives were influenced by hydrostatic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Some adhesives behave differently in tension and compression because of the influence of hydrostatic stress on the nonlinear behaviors. Several experimental investigations involving multiaxial stress states, such as Arcan joints (Bidaud et al 2016;Suwanpakpraek et al 2020), lap shear joints (Srinivasan, Ravichandran, and Idapalapati 2020;Zgoul and Crocombe 2004), scarf joints (Afendi, Teramoto, and Bakri 2011;Carrere et al 2015), and tubular butt joints (Arnaud, Créac'Hcadec, and Cognard 2014;Cognard et al 2012), have shown that the yield and failure of adhesives were influenced by hydrostatic stress.…”
Section: Introductionmentioning
confidence: 99%